Transient electron transport in the ternary alloys AlxGa1-xN, InxGa1-xN, AlxIn1-xN using the Monte Carlo method of simulation - Nadia, Bachi; Chabane-Sari, Nasr Eddine (جامعة الوادي Université ofEl-Oued, 2022)
The transient electron transport and overspeed phenomenon in the binary cubic compounds GaN, InN and AlN and their ternary alloys AlGaN, InGaN and InAlN are examined and compared. For all these alloys, the overspeed phenomenon occurs beyond the critical field at which electrons can pass from the valence band to the conduction band. This field is relatively large for these alloys, particularly when the molar fraction of aluminum is large in the InAlN and AlGaN alloys. This field can reach 500 kV/cm for AlN and it is smaller in alloys with high indium concentration. It is 70 kV/cm for InN. Thus, the critical field for these alloys can vary from kV/cm to 500 kV/cm, including 150 KV/cm for GaN. The overspeed phenomenon becomes greater in the presence of Indium and it is less important in the presence of Aluminum. The present work focuses on the electronic transport in the alloys AlxGa1-xN, InxGa1-xN and InxAl1-xN in the transitional mode by using the Monte Carlo method of simulation which is the most appropriate
Article
Keywords: AlxGa1-xN InxGa1-xN InxAl1-xN Electric transport Monte Carlo method of simulation Transitional mode